Transformasi Kawasan Produktif: Alih Fungsi Lahan sebagai Ruang Pemukiman di Kecamatan Ungaran Timur Kabupaten Semarang - Fathimah Tsabitah Al-Khairiyah; Ali Sofyan (Journal of Religion and Social Transformation, 2024)
Social transformation in post modern era to reap pro and contra for down grade or create important/policy. This research purpose to analyse function change area as a space residence with many other polemical has happened and means cleared to pass policy brief in glasses social movement.  Method for this research used type qualitative approach. The result for research showed social problem is that change area productive forest for residence and cause landslide disaster and to failed social transformation for suggestion the residence difficult conditional. Therefore, surely strongest law by create important/policy and research depth about environment issue and residence or paradigm analyse social movement for cleared hegemony problem named.